Two new species of Hopperia (Nematoda, Comesomatidae) and Metachromadora (Nematoda, Desmodoridae) from Patagonia, Chubut, Argentina - Pastor, Catalina Teresa (2004)
One new Comesomatidae species and one new Desmodoridae species from the Gulfs of San José and San Matías, Chubut province are described: Hopperia patagonica sp. n. is characterized by the shape of odontia on anterior end (one big and two smaller teeth on each); odontia length in relation to the amphid length; values of b and R3, short body length (L: 1370–1500 µm) and the de Man’s ratios ( b: 10.3–11.7). Metachromadora zaixsi sp. n. is characterized by the absence of pre-cloacal supplements, the presence of four cephalic setae and the de Man’s ratios (b: 4.7–7.2). Keys are provided for both species.